2023
DOI: 10.1200/go.22.00360
|View full text |Cite
|
Sign up to set email alerts
|

HIV Prevalence and Characteristics Among Patients With AIDS-Defining and Non–AIDS-Defining Cancers in a Tertiary Hospital in Kenya

Abstract: PURPOSE Antiretroviral therapy (ART) has resulted in a higher life expectancy of persons living with HIV. This has led to an aging population at risk for both non–AIDS-defining cancers (NADCs) and AIDS-defining cancers (ADCs). HIV testing among patients with cancer in Kenya is not routinely performed, making its prevalence undefined. The aim of our study was to determine the prevalence of HIV and the spectrum of malignancies among HIV-positive and HIV-negative patients with cancer attending a tertiary hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Another study in this review found that women with cancer and HIV-infection with lower CD4 cell counts had shorter survival when compared with their HIV-negative counterparts [ 49 ]. The high cancer-related mortality among PLHIV is also linked to late presentation with advanced disease [ 79 ] with six studies [ 40 , 41 , 55 , 60 , 68 , 71 ] in our review reporting that the majority of PLHIV with cancer presented with stages III and IV or advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in this review found that women with cancer and HIV-infection with lower CD4 cell counts had shorter survival when compared with their HIV-negative counterparts [ 49 ]. The high cancer-related mortality among PLHIV is also linked to late presentation with advanced disease [ 79 ] with six studies [ 40 , 41 , 55 , 60 , 68 , 71 ] in our review reporting that the majority of PLHIV with cancer presented with stages III and IV or advanced disease.…”
Section: Discussionmentioning
confidence: 99%